Ablation Threshold Measurement and Chemical Modification of UV Nanosecond Laser Micromachining of Polycrystalline Diamond. Issue 24 (31st October 2021) - Ullah, Naveed; Cui, Jianlei; Dong, Xiangyang; Fang, Xuyang; Dou, Jian; Sun, Zheng; Mei, Xuesong
Abstract : The effects of pulsed laser interaction with matter have become a center for research. The pulsed laser has become an indispensable manufacturing tool in the efficient machining of polycrystalline diamond (PCD) and other materials. Herein, the ablation threshold and chemical modification of PCD irradiated using ultraviolet (UV) nanosecond laser is scrutinized. Using a UV nanosecond laser source, a bulk of PCD is ablated in air, and multipulse processing is executed at a wavelength of 355 nm. The ablation threshold of PCD is reported to be ≈3.7326 J cm −2 based on the linear relationship between the laser pulse energy density and the crater diameter, with a Gaussian distribution of the laser intensity on the cross‐section. Furthermore, the sp 3 structure transitioned to the sp 2 graphite phase when the PCD is exposed to UV nanosecond laser irradiation. Consequently, this study provides a theoretical and experimental reference for UV nanosecond laser micromachining of PCD materials in the research and metal‐working industries. Abstract : Herein, using an ultraviolet (UV) nanosecond laser with a wavelength of 355 nm, the ablation threshold of polycrystalline diamond is measured to be approximately 3.7326 J cm −2 based on laser‐induced crater formation. Furthermore, the transition from the sp 3 structure to the sp 2 graphite phase occurs when the polycrystalline diamond is exposed to UV nanosecond laser irradiation.